The foundations of the Islamic financial industry: A theoretical approach - saad Ouledlaid (Dirassat Journal Economic Issue, 2016)
This paper investigates the question of whether the phenomenon of Islamic finance that based on Shariah, or Islamic law is truly globalizing and spreading as a universal system of finance and banking. The paper also addresses various aspects of the globalization for Islamic finance, among other, the issue of the rise of Islamic banking in the world, Islamic jurisprudence and finance, global standards and integration for Islamic finance, and obstacles facing Islamic finances integration and growth into the global financial system. The paper suggested three elements; the first one is the definition of the Islamic financial industry also and its Important, also its growth in the world wide financial system, and finally the conception of the Islamic financial markets.